A novel approach to fabricate porous alumina ceramics with excellent properties via pore-forming agent combined with sol impregnation technique. Issue 14 (1st October 2018) - Liu, Jingjing; Huo, Wenlong; Ren, Bo; Gan, Ke; Lu, Yuju; Zhang, Xiaoyan; Tang, Xinyue; Yang, Jinlong
Abstract: An innovative approach for fabricating porous alumina ceramics (PACs) with improved mechanical and thermal properties using walnut shell powders as pore-forming agent combined with alumina sol impregnation is reported in the present work. It is demonstrated that uniform distribution of spherical pores can be observed in as-prepared PACs by using above technical route. The decrease of walnut shell powder sizes significantly promotes the enhancement of crushing strength and reduction of thermal conductivity of the PACs. Meanwhile, the impregnated alumina sol is favoring for the formation of spherical micro-pores, then further improves their mechanical and thermal insulation performances. The lowest thermal conductivity and highest crushing strength of resulting sample reach 0.16 W/m K and 29.2 MPa, respectively. This novel method offers new possibilities to fabricate high-quality PACs.